Philosophy of religion - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New jersey : Film For The Humanities & Sciences, 2004)
This program explores three major areas of philosophical inquiry into religion: religious epistemology, or the exploration of the rational grounds for religious beliefs and, in particular, the existence of God; the metaphysics of religion, which inquires into the nature of God; and theodicy, which examines the philosophical implications of the presence of evil in the world. Commentary by Alvin Plantinga, of the University of Notre Dame; Fordham University's Merold Westphal; Dean Zimmerman, of Rutgers University; and Richard Sorabji, of King's College London, is featured. Readings from Thomas Aquinas' Summa Theologica, Moses Maimonides' Guide for the Perplexed, and other essential texts are included
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
Narrator: Liz Chang, Juan Antonio Middleton
DVD format
Keywords: Philosophy; Religion -- Philosophy; Philosophy of religion